Immunity of turbot Induced by inactivated vaccine of Aeromonas salmonicida from the perspective of DNA methylation - Li, Yingrui; Su, Lin; Liu, Xiaofei; Guo, Huimin; Zhou, Shun; Xiu, Yunji (Frontiers in Immunology, 2023)
DNA methylation was one of the most important modification in epigenetics and played an important role in immune response. Since the introduction of Scophthalmus maximus, the scale of breeding has continued to expand, during which diseases caused by various bacteria, viruses and parasites have become increasingly serious. Therefore, the inactivated vaccines have been widely researched and used in the field of aquatic products with its unique advantages. However, the immune mechanism that occurred in turbot after immunization with inactivated vaccine of Aeromonas salmonicida was not clear. This study explored the immune mechanism of turbot after injection of inactivated vaccine of Aeromonas salmonicida from the perspective of DNA methylation. A total of 8149 differentially methylated regions (DMRs) were screened by Whole Genome Bisulfite Sequencing (WGBS), in which there were many immune-related genes with altered DNA methylation status. Meanwhile, Transcriptome sequencing identified 386 significantly differentially expressed genes (DEGs), many of which were significantly enriched in Toll-like receptor signaling pathway, NOD-like receptor signaling pathway and C-type lectin receptor signaling pathway. Combined analysis of WGBS results and RNA-seq results, a total of 9 DMRs of negatively regulated genes are located in the promoter region, including 2 hypermethylated genes with lower expression and 7 hypomethylated genes with higher expression. Then, two immune-related genes C5a anaphylatoxin chemotactic receptor 1-like (C5ar1-Like) and Eosinophil peroxidase-like (EPX-Like), were screened to explore the regulation mechanism of DNA methylation modification on their expression level. Double luciferase report assay and DNA pull-down assay were demonstrated that the DNA methylation state of the gene promoter region affected genes transcriptional activity by inhibiting the binding of transcription factors, which lead to changes in the expression level of the gene. In conclusion, we jointly analyzed WGBS and RNA-seq results and revealed the immune mechanism that occurred in turbot after immunized with inactivated vaccine of A. salmonicida from the perspective of DNA methylation.